1997
DOI: 10.1007/s002130050299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imipramine treatments on the 5-HT 1A -receptor-mediated inhibition of panic-like behaviours in rats

Abstract: The escape behaviour induced in rats by injecting D,L-homocysteic acid (DHL) into the dorsal periaqueductal grey area (DPAG) was used as an animal model of panic attacks to investigate the effect of imipramine, a drug used for the treatment of panic disorder, on the sensitivity of 5-HT1A receptors in the DPAG. Rats given imipramine (10 mg/kg per day SC for 3 weeks or IP for 2-3 days) received 250 nl saline or the 5-HT1A agonist 8-OH-DPAT (8.6 nmol) into the DPAG 10 min before inducing the escape response with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
1
17
2
Order By: Relevance
“…In the same animal model of panic used in this study, facilitation of 5-HT neurotransmission in the DPAG has been reported after long (24 days) but not short-term (6 days) treatment with the antipanic drugs imipramine and fluoxetine (de Bortoli et al 2006;Jacob et al 2002;Mongeau and Marsden 1997). As in the present study, this evidence was gathered after the intra-DPAG injection of 8-OH-DPAT and DOI, suggesting that, in this midbrain area, the reactivity of both 5-HT 1A and 5-HT 2A receptors was enhanced.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In the same animal model of panic used in this study, facilitation of 5-HT neurotransmission in the DPAG has been reported after long (24 days) but not short-term (6 days) treatment with the antipanic drugs imipramine and fluoxetine (de Bortoli et al 2006;Jacob et al 2002;Mongeau and Marsden 1997). As in the present study, this evidence was gathered after the intra-DPAG injection of 8-OH-DPAT and DOI, suggesting that, in this midbrain area, the reactivity of both 5-HT 1A and 5-HT 2A receptors was enhanced.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical results show that these compounds exert their full antipanic effects when given chronically, although the time of onset may vary among the groups; alprazolam, for instance, has a more rapid action than imipramine or fluoxetine (Andersch et al 1991;Kasper and Resinger 2001). In the case of SNRIs and SSRIs, this delayed onset of effect has been taken as an indication that neuroplastic adaptive changes may ultimately underlie their clinically relevant actions (Hensler 2003;Hjorth et al 2000;Jacob et al 2002;Mongeau and Marsden 1997;Zanoveli et al 2005).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These lines of evidence may suggest the presence of diverse HTR2C populations, or, better, the expression of HTR2C receptors in the surface of interneurons embedded in inhibitory or facilitative pathways in the midbrain and limbic forebrain respectively. Antidepressant chronic treatment is effective against anxiety disorders, and it has been associated with modulation in the activity of HTR1A and HTR2A receptors in the midbrain [Mongeau and Marsden, 1997;Jacob et al, 2002;Zanoveli et al, 2005;de Bortoli et al, 2006;Zanoveli et al, 2007], whilst evidence for the HTR2C is sparse and divergent [Jacob et al, 2002;Moreira and Guimaraes, 2005] and further investigations are required. The other relevant structure within the midbrain is the SN, which receives afferences from the dorsolateral striatum, and directly projects to the thalamic motor nuclei.…”
mentioning
confidence: 98%